Concepções e perfil de educadores museais de Mato Grosso do Sul, sob a perspectiva interdisciplinar da educação ambiental crítica - Almeida, Karina da Silva (2023)
Research on museum spaces has highlighted the rise and recognition of their educational potential. However, it is also perceived the concern with certain issues of the organization of these environments. On the other hand, little is known about the formation, conceptions and profile of museum educators. And it was thinking about this lack that this research was proposed, by which it is questioned: Who are the educators of the museums of Mato Grosso do Sul? What are your conceptions about museums and the theme of Environmental Education in this space. Do these educators consider interdisciplinary knowledge to teach? Thus, this research aimed to investigate the profile, conceptions and actions of museum educators from three museums in Mato Grosso do Sul. The research is of qualitative-quantitative approach and the target audience of the investigation is formed by managers and educators, who work in the Museum of Don Bosco Cultures (MCDB), Museum of Archaeology of UFMS (MUARQ) and the Museum of History of the Pantanal (MUHPAN). The data collection instrument used in the research was a semi-structured questionnaire with open and closed questions applied through the Google Forms platform, in addition to a semi-structured interview The data were analyzed through the technique of content analysis (Bardin, 2011), whose dimensions of analysis were selected a priori following the reference of Silva (2007), which classifies three distinct typologies of conceptions of environmental education, they are: Conservative Conception, Pragmatic Conception and Critical Conception. The results showed that in general, museum educators are mostly students, either from undergraduate and/or graduate courses, who have a temporary bond performing the function of interns, or in a smaller number effective bond as professionals. In addition, the research showed that these professionals yearn for improvements and appreciation of their profession. And with regard to the conceptions about interdisciplinarity and environmental education, the results show the existence of conceptual misconceptions, gaps in training and the need for promotion and lack of provision of specific training for this target audience. It is expected that the reflections from this research will foster improvements in the training of museum educators, especially to perform critical Environmental Education, these professionals play an important role in the democratization and popularization of culture and science for the whole society.